Diabetic autonomic neuropathies as a major risk factor for silent myocardial ischemia and infarction: a literature review - Shek Kamara, Kindo; Feng Tong, Chuan (International Journal of Medicine, 2020)
A substantial number of myocardial infarctions (MIs) are asymptomatic or associated with mi-nor and atypical symptoms. These symptoms are often atypical or even absent, especially in di-abetic patients. A number of studies on this topic have shown that in the presence of myocardial ischemia and infarction, diabetic patients report angina less frequently than non-diabetic pa-tients. In this article review, we researched several published articles written about this subject and investigated the relationship between Diabetes Mellitus (DM) in patients and the occur-rence of silent myocardial ischemia and infarction due to the onset of diabetic neuropathy (DN), which is brought about by prolonged diabetes. Based on our research of published articles and studies, we found overwhelming evidence that supports the fact that diabetic autonomic neu-ropathy (DAN) is a major contributing factor in the morbidity of silent myocardial ischemia and infarction among patients suffering from DM.Â Â